TiO2 Nanoparticles in Bulk Heterojunction P3HT-PCBM Organic Solar Cell - Kukreti, Kamlesh; Rathod, Arun Pratap Singh; Kumar, Brijesh (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*351.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907258);" role="presentation">This research paper aims to present a concise, depth insight of organic solar cells. Subsequently, this paper also <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*364.85px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.995801);" role="presentation">discusses various recent advancements in organic solar cells in terms of material, structures and other <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*378.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.853993);" role="presentation">pe<span dir="ltr" style="left: calc(var(–scale-factor)*81.50px); top: calc(var(–scale-factor)*378.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937999);" role="presentation">rformance influencing factors. <span dir="ltr" style="left: calc(var(–scale-factor)*207.53px); top: calc(var(–scale-factor)*378.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946227);" role="presentation">This <span dir="ltr" style="left: calc(var(–scale-factor)*228.53px); top: calc(var(–scale-factor)*378.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942044);" role="presentation">paper reviewed to see the effect of TiO2 <span dir="ltr" style="left: calc(var(–scale-factor)*396.43px); top: calc(var(–scale-factor)*378.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943614);" role="presentation">nano particles on η in the BHJ <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*391.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971806);" role="presentation">polymeric solar cell by its incorporation into the composite active (photovoltaic) layer, comprised of poly3- <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*404.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949734);" role="presentation">hexyl-<span dir="ltr" style="left: calc(var(–scale-factor)*97.46px); top: calc(var(–scale-factor)*404.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.975509);" role="presentation">thiophene P3HT, and [6,6]-<span dir="ltr" style="left: calc(var(–scale-factor)*213.29px); top: calc(var(–scale-factor)*404.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923767);" role="presentation">phenylC<span dir="ltr" style="left: calc(var(–scale-factor)*247.01px); top: calc(var(–scale-factor)*408.05px); font-size: calc(var(–scale-factor)*6.48px); font-family: sans-serif; transform: scaleX(0.9);" role="presentation">61-<span dir="ltr" style="left: calc(var(–scale-factor)*256.85px); top: calc(var(–scale-factor)*404.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942863);" role="presentation">butyricacid-<span dir="ltr" style="left: calc(var(–scale-factor)*305.35px); top: calc(var(–scale-factor)*404.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95466);" role="presentation">methylester (PCBM). Nano-<span dir="ltr" style="left: calc(var(–scale-factor)*422.38px); top: calc(var(–scale-factor)*404.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963456);" role="presentation">structured TiO2 <span dir="ltr" style="left: calc(var(–scale-factor)*490.42px); top: calc(var(–scale-factor)*404.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934948);" role="presentation">exhibits <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*417.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914075);" role="presentation">good proces<span dir="ltr" style="left: calc(var(–scale-factor)*122.18px); top: calc(var(–scale-factor)*417.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964892);" role="presentation">sability, favourable characteristics of the transport of electrons, and brilliant physical as well as <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*430.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.989224);" role="presentation">chemical stability which are important wants in solar cells as impact of blending of TiO2 <span dir="ltr" style="left: calc(var(–scale-factor)*452.74px); top: calc(var(–scale-factor)*430.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954809);" role="presentation">nano particles in <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*444.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912644);" role="presentation">between photo-<span dir="ltr" style="left: calc(var(–scale-factor)*135.02px); top: calc(var(–scale-factor)*444.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940582);" role="presentation">active layers is elucidated the e<span dir="ltr" style="left: calc(var(–scale-factor)*265.85px); top: calc(var(–scale-factor)*444.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960357);" role="presentation">lectrical perfo<span dir="ltr" style="left: calc(var(–scale-factor)*322.87px); top: calc(var(–scale-factor)*444.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951227);" role="presentation">rmance of P3HT-<span dir="ltr" style="left: calc(var(–scale-factor)*395.35px); top: calc(var(–scale-factor)*444.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.966227);" role="presentation">PCBM- <span dir="ltr" style="left: calc(var(–scale-factor)*430.18px); top: calc(var(–scale-factor)*444.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.890598);" role="presentation">based solar <span dir="ltr" style="left: calc(var(–scale-factor)*479.86px); top: calc(var(–scale-factor)*444.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954378);" role="presentation">cells. This <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*457.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905988);" role="presentation">paper relates to bulk hete<span dir="ltr" style="left: calc(var(–scale-factor)*173.42px); top: calc(var(–scale-factor)*457.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927262);" role="presentation">rojunction organic solar cells. More specifically, the enhancement of PCE <span dir="ltr" style="left: calc(var(–scale-factor)*474.22px); top: calc(var(–scale-factor)*457.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934112);" role="presentation">of solar <span dir="ltr" style="left: calc(var(–scale-factor)*507.58px); top: calc(var(–scale-factor)*457.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964667);" role="presentation">cell <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*470.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949391);" role="presentation">based on polymer, using mix of poly 3-<span dir="ltr" style="left: calc(var(–scale-factor)*233.93px); top: calc(var(–scale-factor)*470.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959515);" role="presentation">hexylthio-<span dir="ltr" style="left: calc(var(–scale-factor)*274.97px); top: calc(var(–scale-factor)*470.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933406);" role="presentation">phene(P3HT), derivatives of C<span dir="ltr" style="left: calc(var(–scale-factor)*400.15px); top: calc(var(–scale-factor)*474.19px); font-size: calc(var(–scale-factor)*6.48px); font-family: sans-serif; transform: scaleX(0.9);" role="presentation">60 <span dir="ltr" style="left: calc(var(–scale-factor)*409.75px); top: calc(var(–scale-factor)*470.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951609);" role="presentation">as [6, 6]-<span dir="ltr" style="left: calc(var(–scale-factor)*446.86px); top: calc(var(–scale-factor)*470.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937471);" role="presentation">phenyl C<span dir="ltr" style="left: calc(var(–scale-factor)*483.82px); top: calc(var(–scale-factor)*474.19px); font-size: calc(var(–scale-factor)*6.48px); font-family: sans-serif; transform: scaleX(0.9);" role="presentation">61<span dir="ltr" style="left: calc(var(–scale-factor)*490.30px); top: calc(var(–scale-factor)*470.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963751);" role="presentation">butyric- <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*483.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905338);" role="presentation">acidmethylester <span dir="ltr" style="left: calc(var(–scale-factor)*138.26px); top: calc(var(–scale-factor)*483.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.973217);" role="presentation">(PCBM) <span dir="ltr" style="left: calc(var(–scale-factor)*175.85px); top: calc(var(–scale-factor)*483.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961058);" role="presentation">and TiO2 <span dir="ltr" style="left: calc(var(–scale-factor)*215.81px); top: calc(var(–scale-factor)*483.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906859);" role="presentation">nano particles has been reported. P3HT-<span dir="ltr" style="left: calc(var(–scale-factor)*379.63px); top: calc(var(–scale-factor)*483.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0335);" role="presentation">TiO2 <span dir="ltr" style="left: calc(var(–scale-factor)*402.07px); top: calc(var(–scale-factor)*483.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.894847);" role="presentation">based solar cell has also been <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*497.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910264);" role="presentation">fabricated as <span dir="ltr" style="left: calc(var(–scale-factor)*127.70px); top: calc(var(–scale-factor)*497.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971986);" role="presentation">there is a probability of improvement in η and J<span dir="ltr" style="left: calc(var(–scale-factor)*328.87px); top: calc(var(–scale-factor)*500.71px); font-size: calc(var(–scale-factor)*6.48px); font-family: sans-serif; transform: scaleX(0.928814);" role="presentation">SC <span dir="ltr" style="left: calc(var(–scale-factor)*340.39px); top: calc(var(–scale-factor)*497.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960662);" role="presentation">by optimizing the blending concentration of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*510.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0335);" role="presentation">TiO2 <span dir="ltr" style="left: calc(var(–scale-factor)*93.98px); top: calc(var(–scale-factor)*510.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.868492);" role="presentation">nano pa<span dir="ltr" style="left: calc(var(–scale-factor)*125.30px); top: calc(var(–scale-factor)*510.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937029);" role="presentation">rticles.